2021
DOI: 10.29023/alanyaakademik.697529
|View full text |Cite
|
Sign up to set email alerts
|

Bulanık PERT Yöntemiyle Lojistik İç Taşıma Süreç Analizi

Abstract: ÖZETLojistik süreçlerin en önemli halkalarından biri taşımacılık süreçleridir. Taşımacılık süreçleri, ana taşıma noktası olan terminallere ulaşmayı kapsayan ön taşıma, ana taşıma ve varış terminalinden alıcıya olan ulaşımı kapsayan son taşıma süreçlerinden oluşmaktadır. Ön taşıma ve son taşıma süreçleri genel olarak iç taşıma olarak adlandırılmakla beraber; ön taşımayı ihracat iç taşıma, son taşımayı ise ithalat iç taşıma olarak ifade edebiliriz. Ana taşıma süreci kadar, etkin bir taşıma süreci için iç taşıma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Bruzzone et al (2012) used a simulation model of a real container terminal's process, together with genetic algorithms, to perform a range allocation optimization on the assignment of berths to incoming ships and the number of tractors to serve each dock crane. Bayar and Akan (2020) used Monte Carlo Simulation methods to analyze the business process of ocean freight pricing while Bayar and Akan (2021) used fuzzy program evaluation and review technique (PERT) to analyze the business process of export-import inland haulage in maritime logistics. Borch and Batalden (2015) showed that organizations may need to introduce entrepreneurial BPMJ 29,4 business models with strong links to external actors to tackle the logistics challenges of turbulent environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bruzzone et al (2012) used a simulation model of a real container terminal's process, together with genetic algorithms, to perform a range allocation optimization on the assignment of berths to incoming ships and the number of tractors to serve each dock crane. Bayar and Akan (2020) used Monte Carlo Simulation methods to analyze the business process of ocean freight pricing while Bayar and Akan (2021) used fuzzy program evaluation and review technique (PERT) to analyze the business process of export-import inland haulage in maritime logistics. Borch and Batalden (2015) showed that organizations may need to introduce entrepreneurial BPMJ 29,4 business models with strong links to external actors to tackle the logistics challenges of turbulent environments.…”
Section: Literature Reviewmentioning
confidence: 99%